(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To evaluate the improvement of shoulder joint mobility in patients with periarthritis of the shoulder under the influence of laser acupuncture combined with acupressure. Subjects and Method: A controlled clinical intervention, comparing after and before treatment on 70 patients with periarthritis of the shoulder. Result: After treatment, 45,7% % of patients had normal movement, 54,3% of patients limited movement slightly, no patients had morderate or severe shoulder joint mobility limitations, (p<0.01). Conclusion: Laser acupuncture combined with acupressure therapy was effective in improving shoulder joint mobility in patients with periarthritis of the shoulder.